Woven Images of the Others: Traditional Ayuuk Indigenous Textiles (Mixes) of San Juan Cotzocón, State of Oaxaca, and Their Insertion in Contemporary Mexico. - Tránsito, César A. (Caietele Echinox, 2019)
The Mexican State has maintained a complex relationship with the artistic creations of the Indigenous Mexicans. On the one hand, Indigenous artistic creations are shown as activities that don't require "professional", academic and "scientific" preparation. On the other hand, the same activity is associated with a millennial artistic legacy. Indigenous artistic creations, specifically the textile arts, have gone through different evaluative processes that compared them, in the first years after the Mexican Revolution of 1910, with European artistic manifestations; such evaluation has since then taken a different path, interpreting them as craft objects for tourist consumption. Keywords: Indigenism; Indigenous Textiles; Popular Art; Traditional Art; Ayuuk Imaginary.